If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -69 + 11x = x + 61 Reorder the terms: -69 + 11x = 61 + x Solving -69 + 11x = 61 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -69 + 11x + -1x = 61 + x + -1x Combine like terms: 11x + -1x = 10x -69 + 10x = 61 + x + -1x Combine like terms: x + -1x = 0 -69 + 10x = 61 + 0 -69 + 10x = 61 Add '69' to each side of the equation. -69 + 69 + 10x = 61 + 69 Combine like terms: -69 + 69 = 0 0 + 10x = 61 + 69 10x = 61 + 69 Combine like terms: 61 + 69 = 130 10x = 130 Divide each side by '10'. x = 13 Simplifying x = 13
| w-2-3h=52 | | 8x-14=(x^2)+1 | | 4x+-4x=-1x+-1 | | 61=4x-13 | | -2(x-4)(x+3)=0 | | log^3(x)=log^9(3*x+18) | | 1b=-42 | | 12x+8y=138 | | (X+11)(x+3)=240 | | x*(2x+7)=460 | | 1/3*2.25 | | (3z-5)(3z+15)=0 | | W=(.0026*65*1000*^(3)/1.5 | | 4x+-4=-4x+6 | | 3m+9=4(2m+6) | | -10v=6 | | 22.1+.21x=24.94+.16x | | 12y+9x=294 | | -(x-1)(x-5)(x-10)=0 | | 6sinx+5cosx=2 | | 0.8d+3.74=d+1.5 | | 6+5(-6x+3)=-4 | | 4/n=11 | | -16-10x=-7x+38 | | 90=3.5x | | H/8=3 | | 100=10Q(x)+5Q(Y) | | -5n-24+n^2=0 | | 20/3=m30 | | 2x+18=55 | | -2x^3+7x^2+3x-18=0 | | (6x)^2/3=36 |